New records and a new species of chewing lice (Phthiraptera, Amblycera, Ischnocera) found on Columbidae (Columbiformes) in Pakistan - Naz, Saima (Pensoft Publishers, 2012)
Abstract. The chewing lice (Phthiraptera) of Columbidae (Columbiformes) from Pakistan are studied. Six species of chewing lice with new host records are recorded and one new species of the genus Colpocephalum is described from Columba livia in the Karachi region. All the columbid chewing lice from Pakistan are keyed out and the new species is illustrated and compared with the closest allied species.